EVALUASI KEBIJAKAN PEMBANGUNAN SUMBER DAYA MANUSIA DI WILAYAH PERBATASAN KALIMANTAN TIMUR - RONI, MUT (Pusjar SKPP Lembaga Administrasi Negara, 2008)
Frontier region in such of state have high strategic value, evaluated from ideology aspect, political, social, economic, culture, state security and defence. The think mentioned above, now newly get serious attention, after changing over status of Sipadan and Ligitan Island from NKRI to state of Malaysia and also caught up with will grab of Block Ambalat and Karang Unarang by state of Malaysia. This research conducted in order to strengthening regional function frontier of Republic Of Indonesia especially in East Kalimantan Province, passing development of human resource, felt progressively insist on its requirement. In the end this study meant to give recommendation to related other party and government, about strategy and step able to quicken execution of program development of economics in frontier region in general and in area development of human resource especially. Keywords: wilayah perbatasan, pembanguanan sumber daya manusia, Kalimantan Timur.